Mulheres e uma política de proteção em meio à violência : olhares sobre a Rede Lilás na cidade de Porto Alegre - RS - Silva, Camila da Costa (2017)
This work investigates the perception of women who used the services of the Rede Lilás – Network of Coping and Specialised Support to Women and Girls who suffered Domestic Violence, a local articulation which comprises several institutions in Porto Alegre (RS), such as the Women Police Station, The General Institute of Criminal Investigation, The Jury of Family and Domestic Violence Against Women, the Centre of Reference and Social Assistance (CRAS) and the Military Brigade, responsible for the Maria da Penha Patrol, which makes regular visits to victims of violence as protective measures. The initiative is praised by organizations and social movements, the National Justice Council (CNJ) and it stands as an innovative action in terms of coping with violence. Five years after the implementation of the policy, this work is based on interviews with users in order to know stories and perceptions regarding the effect of the institutional practices in their daily lives. Through the intersection of so many formative factors of social realities, what we intend is to understand aspects and views about violence against women in their particularities - the way in which each one lives and experiences it - not disregarding the conditions in which the social relations of gender are historically constructed and, more, in the social context in which they occur: offering perspectives on public policy from the lines of an audience which is their reason.